Pengaruh Pendidikan Pemustaka terhadap Penelusuran Informasi di Perpustakaan Umum Daerah Kota Payakumbuh - Afifah, Nur; Desriyeni, Desriyeni (YASIN, 2025)
Effective information retrieval is an essential skill for library users in the digital era; however, a gap remains in the optimal utilization of library services. This study aims to analyze the influence of user education on information retrieval skills at the Public Library of Kota Payakumbuh. Employing a quantitative approach with a descriptive method, data were collected through observation, questionnaires, and literature review from 63 respondents selected via simple random sampling. The primary instrument, a questionnaire was tested for validity and reliability using SPSS version 25. Data analysis included editing, tabulation, descriptive analysis, and conclusion drawing. The results show that user education is in the good category with an average score of 3.06, reflecting adequate understanding of library services, including OPAC use and reference services. Meanwhile, information retrieval ability is categorized as very good, with an average score of 3.36, indicating users’ proficiency in identifying credible sources, evaluating information relevance, and utilizing various sources effectively. These findings confirm that user education positively influences information retrieval ability. The practical implications highlight the importance of strengthening information literacy programs to enhance library service effectiveness and promote user independence in accessing information.